Adult Attachment, Love Styles, Relationship Experiences and Subjective Well-Being: Cross-Cultural and Gender Comparison between Americans, Portuguese, and Mozambicans - Galinha, Iolanda Costa (2014)
Attachment security, love styles, and romantic relationship experiences are closely associated with subjective well-being (SWB). A few studies have empirically observed significant relations between these variables. However, no studies have included all of these predictors to analyze the unique contribution of each to SWB, and no cross-cultural studies have analyzed these variables simultaneously. This article examined (a) the relations between attachment security, love styles, romantic relationship experiences and subjective well-being, (b) the unique contribution of each to predict SWB, and (c) cross-cultural and gender differences in the predictors of SWB across three samples of 1,574 university students: 497 from North Carolina (US), 544 from Maputo (Mozambique), and 533 from Lisbon (Portugal). We found cross-cultural differences in the three samples. The main predictor of SWB was attachment security in the US and Portuguese samples, while in the Mozambican it was eros love style. Storge love style positively predicted SWB in the US and Portuguese samples, but not in the Mozambican. In contrast, mania love style predicted the SWB of Mozambicans but not that of Americans or Portuguese. We found gender similarities and differences: the association between attachment security and SWB was not gender-specific; the associations between love styles, relationship experiences and SWB were gender-specific.